The Contribution of Degenerate Electron Pressure to The Stability of The Outer Region of Thin Keplerian Accretion Disks Around a Neutron Star (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The stability analysis of a geometrically thin, gas-pressure dominated accretion disk aroundÂ a neutron star is presented. In purely radial perturbation case, thin disk is stable to thermal modes. The stability is analyzed at a small temperature, that is temperature approaching zero and at definite temperature. The contribution of both fully and partially degenerate electrons pressure for the stability of the disk in its outer region is investigated. We find that the disk is stable in this region, where the gas pressure is more dominant than radiation pressure.